Patient reported outcomes in prospective cohort study of Electrochemotherapy. (April 2018) - Al-Hadithy, N.; Dehnel, Alexandra; George, Alexander; Kisiel, Robert; Lunt, Craig; Stone, Christopher
Abstract: Metastatic spread of malignant tumours to skin is a well described phenomenon with incidence of approximately 0.7–9% of all metastases depending on histological type of primary cancer. Electrochemotherapy (ECT) is an efficient local tumour ablation modality that has proven clinical efficacy in the treatment of various types of tumours metastasis to skin. Aims of this study are to evaluate the activity, toxicity, and feasibility of treating patients with electrochemotherapy (ECT); their clinical outcomes and patient report outcome measures. This was a cohort study of 48 patients. In this study a good or excellent response to treatment was observed in 74% of patients on the basis of the clinical photographs. Five patients had partial responses (14%) and three patients had no response (8.5%). One patient died during the study period (2.8%). 87% of patients said they would have ECT again if clinically indicated. Spearman's' rank correlation of clinical efficacy for anatomical location was found to be positive with poorer outcomes in head and neck compared to trunk and limbs. Complications were found in 16patients, of which all were either grade 1 or 2 Clavien classification. The complications were predominantly in patients treated with ECT for tumours the head and neck area. Initial assessment of applicable patient report outcome measures for our patient cohort demonstrate that there are no validated tools exist for ECT. Further work is required here. Highlights: Metastatic spread of malignant tumours to skin is a well described phenomenon with incidence of approximately 0.7–9% of all metastases depending on histological type of primary cancer. Electrochemotherapy (ECT) is an efficient local tumour ablation modality that has proven clinical efficacy in the treatment of various types of tumours metastasis to skin. ECT combines the delivery of a chemotherapeutic agent, usually bleomycin, with 'electroporation'. Electroporation uses short, high‐voltage pulses to transiently permeabilise the cell membrane to deliver non-permeant or poorly permeant chemotherapeutic agents into the cells. ECT can be a treatment for metastatic breast cancer, soft tissue sarcoma, squamous cell cancer, basal cell cancer and malignant melanoma. 87% of patients said they would have ECT again if clinically indicated. A good or excellent response to treatment was observed in 74% of patients.